Renal function in brain dead patients with respect to transplantation - Vlcek, J; Schück, O; Kocandrle, V (Physiologia Bohemoslovaca, 1982)
We examined the renal function in 18 brain dead patients 2-0 h before removing the kidneys and 72 h after their transplantation to the recipient. The kidneys were preserved by simple hypothermia. In brain dead patients we found no demonstrable relationships between PCr and CCr or between Purea and CCr. At this time the Purea and PCr values are not a sufficiently accurate indicator of renal function. We also examined the plasma and urinary concentrations of Na, K, urea and osmotically active substances and calculated their excretion fractions. We found that, prior to removal, the kidneys were in a state of combined osmotic and water diuresis. The osmotic diuresis was chiefly of a non-sodium type and was produced by a mannitol load. Water diuresis was evidently caused by inhibition of ADH output consequent to brain hypoxia. We also investigated the relationship between the CCr values before nephrectomy and in the early posttransplantation phase. We found that there was a relationship between the recipient's CCr values in the early posttransplantation period and donor's CCr/total ischaemic time index. Calculation of this index can be valuable, especially in high risk transplantations.
Keywords: dospělí; Kidney; draslík; Sodium; Female; předškolní dítě; močovina; Potassium; Adult; ženské pohlaví; Adolescent; lidé; Brain Death; Osmolar Concentration; Nephrectomy; transplantace ledvin; osmolární koncentrace; Kidney Transplantation; Male; mozková smrt; sodík; Child, Preschool; Kidney Function Tests; Creatinine; vyšetření funkce ledvin; kreatinin; mužské pohlaví; ledviny; Urea; mladiství; nefrektomie; Humans